FOXA2 controls the cis‐regulatory networks of pancreatic cancer cells in a differentiation grade‐specific manner. (17th September 2019) - Milan, Marta; Balestrieri, Chiara; Alfarano, Gabriele; Polletti, Sara; Prosperini, Elena; Spaggiari, Paola; Zerbi, Alessandro; Diaferia, Giuseppe R; Natoli, Gioacchino
Abstract: Differentiation of normal and tumor cells is controlled by regulatory networks enforced by lineage‐determining transcription factors (TFs). Among them, TFs such as FOXA1/2 bind naïve chromatin and induce its accessibility, thus establishing new gene regulatory networks. Pancreatic ductal adenocarcinoma (PDAC) is characterized by the coexistence of well‐ and poorly differentiated cells at all stages of disease. How the transcriptional networks determining such massive cellular heterogeneity are established remains to be determined. We found that FOXA2, a TF controlling pancreas specification, broadly contributed to the cis ‐regulatory networks of PDACs. Despite being expressed in both well‐ and poorly differentiated PDAC cells, FOXA2 displayed extensively different genomic distributions and controlled distinct gene expression programs. Grade‐specific functions of FOXA2 depended on its partnership with TFs whose expression varied depending on the differentiation grade. These data suggest that FOXA2 contributes to the regulatory networks of heterogeneous PDAC cells via interactions with alternative partner TFs. Synopsis: Pancreatic ductal adenocarcinoma (PDAC) exhibit high differentiation heterogeneity at all stages of the disease, but how transcription factors determine the differentiation status remains unclear. Here, the lineage specification factor FOXA2 is shown to bind target genes in a context‐dependent manner to control alternative gene expression programs via interaction with different transcription factors. FOXA2 is expressed in all differentiation stages of human PDACs. FOXA2 genomic distribution and transcriptome are partially grade‐specific. HNF1beta and HOXB8 are FOXA2 binding partners in well‐ and poorly‐differentiated PDAC cells, respectively. HNF1beta depletion alters the FOXA2 cistrome. Abstract : Interaction with specific transcription factors drives distinct occupancy of FOXA2 at gene sets expressed in well‐ versus poorly‐differentiated pancreatic ductal adenocarcinoma cells.